2022
DOI: 10.3389/fphys.2022.971424
|View full text |Cite
|
Sign up to set email alerts
|

Protections of transcription factor BACH2 and natural product myricetin against pathological cardiac hypertrophy and dysfunction

Abstract: Pathological hypertrophic myocardium under consistent adverse stimuli eventually can cause heart failure. This study aims to explore the role of BACH2, a member of the basic region leucine zipper transcription factor family, in cardiac hypertrophy and failure. Transverse aortic constriction surgery was operated to induce cardiac hypertrophy and failure in mice. BACH2 was overexpressed in mice through tail vein injection of AAV9-Bach2. Mice with systemic or cardiac-specific knockdown of Bach2 were adopted. Neon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…The transverse aortic constriction (TAC) procedure was the same as in our previous study [ 17 ]. After surgery, mice were treated with intragastric myricetin (200 mg/kg/day) or vehicle for 4 weeks.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The transverse aortic constriction (TAC) procedure was the same as in our previous study [ 17 ]. After surgery, mice were treated with intragastric myricetin (200 mg/kg/day) or vehicle for 4 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…Myricetin is a plant-derived flavonoid with cardioprotective effects [ 14 , 15 , 16 ]. Our previous study, alongside others, found that myricetin can ameliorate pressure overload-induced LVH through the BTB domain and CNC homolog 2 (BACH2)/A-kinase anchoring protein 6 (AKAP6) pathway [ 17 ] or NFE2-like bZIP transcription factor 2 (Nrf2) and JUN N-terminal kinase 1/2 (JNK1/2) signaling pathway [ 18 ]. Moreover, chronic administration of myricetin ameliorated hypertension in different animal models [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…As discussed previously, TBI originates from primary injuries, most commonly induced by external injuries, and then gradually evolves into secondary damage, accompanied with inflammatory responses, oxidative stress, and cell death [87]. During TBI progression, these biological processes cooperate with mitophagy to maintain proper mitochondrial quality, which determines the fate neurons.…”
Section: Role Of Mitophagy In Tbimentioning
confidence: 97%
“…There is growing evidence that inhibiting cardiac hypertrophy helps prevent its transition to heart failure. , The present clinical management of cardiac hypertrophy is still difficult because there are no efficient medications. Many natural compounds derived from plants have been investigated for their effects on cardiac hypertrophy in recent years. , Diterpenoids, in particular, offer therapeutic potential for reducing ventricular hypertrophy. …”
mentioning
confidence: 99%